(untitled) (Revista de Ensino em Artes, Moda e Design, 2023)
The objective is to analyze a set of articles from Donna magazine whose main theme is fashion related to fat women from the perspective of the place of speech. Donna is a women’s magazine from Porto Alegre - RS, sold together with the newspaper Zero Hora since 1993. The corpus is a cut of publications from 2016 to 2019, which corresponds to the editorial repositioning of the magazine, which took place in 2017, whose theme focuses on “female diversity” and on what the journal called “real women”. I have as central questions: in what ways does Donna authorize the existence of fat women related to fashion? What are the main themes with the presence of fat women in the fashion section? As main problematizations, I could see the insertion of fat women related to claims for the right of inclusion in the consumer society, in the media and in fashion, with the celebration of bodies said to be “out of standard”, through the aesthetic enhancement and the possibility of access a “thin world”. These are actions guided by individual movements and, despite the celebration of “plus size pride” and the deconstruction of beauty standards, there is a fat body standardized by fashion, the market and the media – a fat media body. What I call an adequate fat woman, a light fat woman – plus size models inserted in the mass media and social networks, and in a universe and “plus size lifestyle”, conquered by the freedom to be beautiful, to consume, to have a sex life and professional success.